2019
DOI: 10.20960/nh.02630
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorders risk assessment on semi-professional male team sports players

Abstract: Introduction: Cardiovascular diseases are the most important cause of death worldwide. The etiology is multifactorial, they may be influenced by various factors such as diet, lifestyle, level of exercise or genetics. The large number of genes involved, as well as its various forms, can influence the risk of cardiovascular diseases through different forms. Aim: To determine the relationship between different genetic polymorphisms and individual risk of CHD in child and adult population. Methods: A literature se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 64 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Based on the results obtained from the equation models, it is observed that for participants with medium and low adherence, there is a negative relationship between anxiety and task climate, but for participants with optimal adherence, there is a positive relationship between the two variables. In view of these findings, Baldó-Vela and Bonfanti [ 49 ] state that weight loss disorders lead to food restriction in order to lose weight quickly, generating an increase in anxiety levels [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results obtained from the equation models, it is observed that for participants with medium and low adherence, there is a negative relationship between anxiety and task climate, but for participants with optimal adherence, there is a positive relationship between the two variables. In view of these findings, Baldó-Vela and Bonfanti [ 49 ] state that weight loss disorders lead to food restriction in order to lose weight quickly, generating an increase in anxiety levels [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Mediterranean Diet is valued for the wide range of benefits it provides, as it is characterized by a high content of essential nutrients and micronutrients. Several studies have shown that these nutrients have an important chemical-preventive role on oxidative stress [ 22 ]. On the other hand, one food group with a high anthocyanin content is red fruits.…”
Section: Introductionmentioning
confidence: 99%